HAK IMUNITAS ADVOKAT INDONESIA DALAM PERSPEKTIF PENEGAKKAN HUKUM DAN KEADILAN DI ERA REVOLUSI INDUSTRI 4.0â€ - Jiwantara, Firzhal Arzhi (Jurnal Muhakkamah, 2019)
ince the birth of Law Number 18 Year 2003 Regarding Advocates on December 21, 2004, it is a form of appreciation for Advocates who are not only working but struggling to find noble justice and until finally being recognized as a Profession. Then from Law Number 18 Concerning Advocates contained the "Immunity Rights" contained in Article 16 which said Advocates could not be prosecuted both civil and criminal in carrying out their professional duties in good faith for the Client's defense in a court hearing ". Advocate is a profession honorable law (officium mobile) where the procedure of work is regulated in the Advocate Professional Ethics Code and Law Number 18 Year 2003 concerning Advocates. In the Act, Advocates have legal rights that make themselves immune from legal remedies on matters relating to the work of their Advocates. This immunity right is important related to its role in the process of law enforcement and the rights of its entity which are independently separated from the client. To maintain the right of immunity to advocates based on Law Number 18 of 2003 concerning Advocates and Constitutional Court Decree Number 26 / PUU-XI / 2013 so that they are free to carry out their profession as law enforcers in Indonesia for the benefit of clients in good faith in the Industrial Revolution Era 4.0.